SCANNING ELECTRON MICROSCOPY OF CANDIDA ALBICANS CELL WALL ON TOOTH SURFACE AFTER FLUCONAZOLE-TREATED AND INCUBATED WITH GUAVA (PSIDIUM GUAJAVA L) - Abdillah Imron Nasution; Basri Basri (Journal of Syiah Kuala Dentistry Society, 2017)
The Candida albicans cell wall is a target of fluconazole. The content of guava (Psidium guajava L) known have contribute factors to resistance of fluconazole. Objective: characterize the surface alterations and the general shape changes of candida cells after in vitro exposure to fluconazole and guava. Material and Methods: six tooth specimen groups: Cells exposed without fungicidal doses (Negative Control), Positive Cells exposed to maximal fungicidal doses of Fluconazole (100g/ml) (Control), Guava (G), Guava+Fluconazole susceptibility (GFS), Guava+Fluconazole Susceptible-Dose Dependent (GFSDD), Guava+Fluconazole dose Resistance (GFR). Each group mixed with 10 ml artificial saliva, 2 ml glucose 2%, and 2 ml C. albicans. Fluconazole doses based on NCCLS approved M27-A. Scaninng Electron Microscopy conducted after 15 days incubation at Faculty of Veterinary University of Syiah Kuala and Faculty of Engineering University of Indonesia. Results, SEM of Negative Control presented smooth of blastospores; small clusters of interconnected cells, spherical to elongate in shape, lying down, polar buds, and hyphae on dental surface. SEM of Positive Control and Guava generally presented: wrinkled of blastospores, rough surfaces, cells fewer than Negative Control, and lying apart. Positive Control showed spherical to elongate in shape and Guava with spherical in shape presented more wrinkled than Positive Control. SEM of GGF and Guava+Fluconazole Susceptible-Dose Dependent presented wrinkled of blastospores, rough surfaces, decreased in number, spherical to elongate in shape, lying apart, and hyphae on surface. SEM of Guava+Fluconazole dose Resistance presented wrinkled of blastospores but more smooth than others, elongate in shape; buds orientations penetrate to dental tissue. Conclusion: Guava improving the integrity of cell wall of Candida albicans and contributed to resistance of Candida albicans to fluconazole.Keywords: Candida albicans, Guava, Fluconazole, Scanning Electron Microscopy